Tourism as a Catalyst for Poverty Reduction in Nepal - Pathak, Jagat Raj; Oli, Lok Bahadur; Pant, Ram Kumar (Academia Research Journal, 2025)
This research entitled tourism and poverty reduction with prospects of tourism in poverty reduction traces the tourism statistics of Nepal. This study is based on secondary data that has revealed huge prospects of tourism in poverty reduction of Nepal. This research has employed descriptive qualitative method. This research has explained the prospects of tourism and its contribution in poverty reduction. This research has found that tourism in Nepal has huge prospects and is in rising trend. In the whole spectrum of tourism, Nepal is making huge progress to attract number of tourists with significant increase in tourists’ arrivals from different countries with slight increase in length of stay. The highest tourists’ numbers are from India. From overseas foreign countries, American nationals are the highest in percentage i.e. 9.89 and followed by British 5.21 percentage in second position. Nepal’s tourism industry is flourishing with increased high income of the nation after the Pandemic- 19. The current tourism is revitalizing its situation with improved condition and facilities making remarkable growth rate 65.05 percentages in the history of tourism of Nepal. The increase in tourists’ number would work as a catalyst in poverty reduction with effective growth in the economic sectors of the nation.